Recent Advances in the Theory and Application of Nanofiltration: a Review - DU, Yuchen; Pramanik, Biplob Kumar; Zhang, Yang; Dumée, Ludovic; Jegatheesan, Veeriah (Current pollution reports, 2022)
Water is the material basis for living organisms and one of the primary resources to maintain the sustainable development of the earth’s ecological environment. As a water purification method, nanofiltration (NF) separation technology has been widely considered by researchers in recent years. However, most of the studies on NF in the literature focus on membrane modification, and there are only a few reviews available. In this paper, the latest research progress of NF is reviewed, and the processes of NF membrane preparation using phase inversion, layer by layer, and interfacial polymerization are described. Polymer materials used for NF membrane preparation are reviewed and the main types of nanofillers to generate thin film nanocomposite membranes, including metal organic frameworks, boron nitride, Ti 3 C 2 T X , graphene oxide, SiO 2 , and iron oxide are discussed. Membrane fouling is inevitable during NF operation and this paper analyzes the mechanisms of fouling and summarizes key pretreatment and cleaning methods required to remediate the long-term effects of cake layer formation. The steric hindrance effect, Donnan effect, and dielectric exclusion are analyzed, and some common characterization methods are summarized. The practical applications of NF are briefly introduced including groundwater, pharmaceutical wastewater, and textile wastewater treatment. Finally, the shortcomings and prospects of the existing research progress are put forward.